Diabetes‐induced mechanophysiological changes in the esophagus. Issue 1 (6th August 2016) - Zhao, Jingbo; Gregersen, Hans
Abstract : Esophageal disorders are common in diabetes mellitus (DM) patients. DM induces mechanostructural remodeling in the esophagus of humans and animal models. The remodeling is related to esophageal sensorimotor abnormalities and to symptoms frequently encountered by DM patients. For example, gastroesophageal reflux disease (GERD) is a common disorder associated with DM. This review addresses diabetic remodeling of esophageal properties and function in light of the Esophagiome, a scientifically based modeling effort to describe the physiological dynamics of the normal, intact esophagus built upon interdisciplinary approaches with applications for esophageal disease. Unraveling the structural, biomechanical, and sensory remodeling of the esophagus in DM must be based on a multidisciplinary approach that can bridge the knowledge from a variety of scientific disciplines. The first focus of this review is DM‐induced morphodynamic and biomechanical remodeling in the esophagus. Second, we review the sensorimotor dysfunction in DM and how it relates to esophageal remodeling. Finally, we discuss the clinical consequences of DM‐induced esophageal remodeling, especially in relation to GERD. The ultimate aim is to increase the understanding of DM‐induced remodeling of esophageal structure and sensorimotor function in order to assist clinicians to better understand the esophageal disorders induced by DM and to develop better treatments for those patients.